(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This text is a small tribute based on memories that the author shared with maestro Juan Francisco Sans, it is therefore a testimonial text that only aims to attest to what this master represented for the Venezuelan music of the twentieth and twentyfirst centuries in his capacity as musicologist, composer, pianist, conductor and cultural promoter.